2018
DOI: 10.3390/ijerph15050881
|View full text |Cite
|
Sign up to set email alerts
|

Employee Perceptions of Workplace Health Promotion Programs: Comparison of a Tailored, Semi-Tailored, and Standardized Approach

Abstract: In the design of workplace health promotion programs (WHPPs), employee perceptions represent an integral variable which is predicted to translate into rate of user engagement (i.e., participation) and program loyalty. This study evaluated employee perceptions of three workplace health programs promoting nutritional consumption and physical activity. Programs included: (1) an individually tailored consultation with an exercise physiologist and dietitian; (2) a semi-tailored 12-week SMS health message program; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
0
12
2
Order By: Relevance
“…Similarly, a study in an Australian transport company found that personal communication and the physical presence of a healthcare specialist (i.e. a registered dietitian or exercise physiologist) were evaluated highly by the employees participating in such programmes [29].…”
Section: Perceptions Regarding Whppsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a study in an Australian transport company found that personal communication and the physical presence of a healthcare specialist (i.e. a registered dietitian or exercise physiologist) were evaluated highly by the employees participating in such programmes [29].…”
Section: Perceptions Regarding Whppsmentioning
confidence: 99%
“…Concerning effectiveness, a recent meta-analysis showed that WHPPs produced little to no effect on health behaviour [23], possibly the result of generally low levels of compliance, which underscores the importance of understanding WHPP participation. This finding suggests it is important to gain insight into their perceptions of WHPP participation and programme characteristics to understand employee characteristics that facilitate or hinder participation [29]. Prior studies have shown that participants of WHPPs should be involved in the design process to enable successful recruitment [30] and improve the programmes' reach and compliance [31].…”
Section: Introductionmentioning
confidence: 99%
“…smoking, diet [7]. Some studies indicate that tailored or individualized WHP initiatives have proven to be more successful than semi-tailored or general programs [21], however these initiatives can be resource intensive.…”
Section: Examples Of Workplace Health Initiatives and Activity-based mentioning
confidence: 99%
“… 7 - 9 Employees participating in WHPPs reduce their health risks and serve as health promotion advocates. 10 Furthermore, WHPPs also efficiently promote cancer prevention and decrease the incidence of heart diseases. 11 Using smart phone-based application (App) software as the supporting material for reminding employees at the workplace to drink water, this study aimed to provide an overview of the effectiveness of health promotion interventions at the workplace on physical and mental health outcomes related to physical fitness and self-satisfaction.…”
Section: Introductionmentioning
confidence: 99%